Mapping the Global Landscape of Enterprise Risk Management Implementation Public Sector: A Bibliometric Study - Rizki Fauziah; Umanto (LPPM Undiksha, 2025)
The core issues addressed in this study concern the low level of management support, difficulties in determining risk values and associated costs, and organizational resistance to change in the implementation of Enterprise Risk Management (ERM) within the public sector. The primary objective of this research is to analyze, evaluate, and synthesize the existing literature on ERM in the public sector in order to develop a more comprehensive understanding of the integration of regulatory frameworks, organizational culture, and internal control systems. This study adopts a qualitative research approach using a Systematic Literature Review (SLR) design based on PRISMA guidelines, combined with bibliometric analysis. The research corpus consists of 229 international articles indexed in Scopus, without involving human research subjects. Data were collected through a rigorous literature selection process using strict inclusion and exclusion criteria, supported by a literature validation matrix to ensure the relevance and quality of the selected studies. Data analysis was conducted using VOSviewer version 1.6.20 and content analysis techniques. The findings indicate that ERM implementation in the public sector remains largely administrative in nature and has not yet been fully integrated with institutional strategy, organizational culture, or consistent regulatory support. The study concludes that effective ERM practices require adaptive, collaborative, and technology-driven approaches to strengthen risk management effectiveness in the public sector. The implications of this research highlight the importance of developing a more contextualized conceptual framework for ERM implementation.